2014
DOI: 10.1142/s1793545813500557
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet-Based Analysis of Cerebrovascular Dynamics in Newborn Rats With Intracranial Hemorrhages

Abstract: Intracranial hemorrhage (IH) is a major problem of neonatal intensive care. The incidence of IH is typically asymptomatic and cannot be e®ectively detected by standard diagnostic methods. The mechanisms underlying IH are unknown but there is evidence that stress-induced disorders in adrenergic regulation of cerebral venous blood°ow (CVBF) are among the main reasons. Quantitative and qualitative assessment of CVBF could signi¯cantly advance understanding of the nature of IH in newborns. In this work, we analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…LSCI experimental data allowed us to understand that accumulation of extensive blood in venous network is a crucial factor for stress-induced critical changes in cerebral vessels related to intracranial hemorrhages. [23][24][25] With LSCI, we also found that the cerebral veins are more sensitive to adrenergic stimulation under normal state and during stress. Full-¯eld imaging of cerebral vessels in rats represents an important new insight in our understanding how the brain responds to stress: after stress-induced intracranial hemorrhages, rats demonstrate a typical venous relaxation due to activation of a special type of vascular receptors \anarchists" that are stimulated by adrenalinethe main hormone of stress but not nervous system.…”
Section: Introductionmentioning
confidence: 59%
“…LSCI experimental data allowed us to understand that accumulation of extensive blood in venous network is a crucial factor for stress-induced critical changes in cerebral vessels related to intracranial hemorrhages. [23][24][25] With LSCI, we also found that the cerebral veins are more sensitive to adrenergic stimulation under normal state and during stress. Full-¯eld imaging of cerebral vessels in rats represents an important new insight in our understanding how the brain responds to stress: after stress-induced intracranial hemorrhages, rats demonstrate a typical venous relaxation due to activation of a special type of vascular receptors \anarchists" that are stimulated by adrenalinethe main hormone of stress but not nervous system.…”
Section: Introductionmentioning
confidence: 59%
“…Effectively used in image formation and processing, wavelet analysis was applied in OCT for noise reduction. [49][50][51][52] Wavelet kernels and optical wave packets demonstrate similar physical features: zero means value, finite energy corresponding to square norm one, and high locality in both time and frequency domains. The wavelet analysis seems to be optimal for the decomposition of time-domain optical data and, in particular, for the denoising of OCT images.…”
Section: Introductionmentioning
confidence: 94%
“…The majority of cases of the spontaneous intracranial hypotension are related to the suppression of the blood outflow from the brain and the elevations of cerebral venous blood pressure that contribute to the occurrence of ICH in newborns (Volpe 2008, Gupta et al 2009. Our recent studies (Semyachkina-Glushkovskaya et al 2013a, Pavlov et al 2014) performed in newborn rats with stress-induced ICH showed that the dilation of the superior sagittal sinus with the fall of velocity of blood flow precedes the incidence of ICH. In adult rats with ICH we found similar pathological changes in cerebral hemodynamics observed at the transient state of ICH while the alteration in the arterial tree was detected only in rats with ICH (Semyachkina-Glushkovskaya et al 2013b).…”
Section: Introductionmentioning
confidence: 98%